2016
DOI: 10.1073/pnas.1515526113
|View full text |Cite
|
Sign up to set email alerts
|

Targeted axonal import (TAxI) peptide delivers functional proteins into spinal cord motor neurons after peripheral administration

Abstract: A significant unmet need in treating neurodegenerative disease is effective methods for delivery of biologic drugs, such as peptides, proteins, or nucleic acids into the central nervous system (CNS). To date, there are no operative technologies for the delivery of macromolecular drugs to the CNS via peripheral administration routes. Using an in vivo phage-display screen, we identify a peptide, targeted axonal import (TAxI), that enriched recombinant bacteriophage accumulation and delivered protein cargo into s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 41 publications
(42 reference statements)
0
34
0
Order By: Relevance
“…Sellers et al identified a different peptide, the targeted axonal import (TAxI) peptide, which enriched recombinant bacteriophage accumulation and delivered an active enzyme into spinal cord motor neurons in the aftermath of an intramuscular injection in mice [155]. According to the authors, the TAxI peptide showed great potential for clinics, since it can also interact with human spinal cord motor neurons.…”
Section: Peptidesmentioning
confidence: 99%
“…Sellers et al identified a different peptide, the targeted axonal import (TAxI) peptide, which enriched recombinant bacteriophage accumulation and delivered an active enzyme into spinal cord motor neurons in the aftermath of an intramuscular injection in mice [155]. According to the authors, the TAxI peptide showed great potential for clinics, since it can also interact with human spinal cord motor neurons.…”
Section: Peptidesmentioning
confidence: 99%
“…Regenerative medicine intended vascular homing peptides have been described towards specific clinical situations, such as targeting blood clots that form after an acute, traumatic tissue injury [33] or towards angiogenetic blood vessels at early [34] and late stage of wound healing when granulation tissue matures to scar tissue [26]. In addition to these, homing peptide targeting tissue factor after blood vessel rupture has been used to deliver amphiphile nanofibers to control hemorrhage [35], targeted axonal import peptide delivered therapeutic recombinant proteins to transected nerves after spinal cord injury [36]. Homing peptides that seek out burn injury in intestine [37,38] or deliver diagnostic or therapeutic nanoparticle to brain injury after a traumatic breakage of the blood-brain barrier [39,40] have been described.…”
Section: Ligands Targeting Injured Tissuesmentioning
confidence: 99%
“…can be applied to all injuries, such as identifying peptides capable of binding to the angiogenic or inflammatory blood vessels forming at the injured tissues [24] , or peptides binding to the extracellular matrix (ECM) collagen exposed in inflammatory conditions [30] . Additional targeting peptides have been described towards more specific clinical molecular targets such as blood clots after an injury [31] , angiogenetic blood vessels at early [32] and late stage of wound healing when granulation tissue matures to scar tissue [24] , ruptured blood vessels [33] , transected nerves [34] , intestine with burn injury [35,36] , brain injury after a traumatic breakage of the blood-brain barrier [37,38] , bone tissue [39][40][41] , bacterial infections [42] or simply illuminating neural structures during surgery [43,44] (Table 1).…”
Section: Ligands Targeting Injured Tissuesmentioning
confidence: 99%